Managing adaptive pervasive computing using knowledge-based service integration and rule-based behavior - Wade, Vincent; Conlan, Owen; O'Sullivan, Declan; Lewis, David (My University, 2004)
Managing adaptive pervasive computing using knowledge-based service integration and rule-based behavior
IFIP/IEEE Network Operations and Management Symposium (NOMS 2004)
PUBLISHED
Seoul, Korea
Keywords: Non-controlled Indexing; Digital Engagement; Telecommunications